Controllable Preparation of Al2O3‐MgO·Al2O3‐CaO·6Al2O3 (AMC) Composite with Improved Slag Penetration Resistance. Issue 1 (8th July 2015) - Chen, Junhong; Yan, Mingwei; Su, Jindong; Li, Bin; Chou, Kuo‐Chih; Hou, Xinmei; Chen, Mao; Zhao, Baojun
Abstract : Compact Al2 O3 ‐MgO·Al2 O3 ‐CaO·6Al2 O3 (AMC) composite was obtained by melting technology using industrial alumina, light‐burned magnesia, and quick lime as raw materials based on the Al2 O3 ‐MgO‐CaO ternary phase diagram. The results show that the phases of MgO·Al2 O3 and Al2 O3 are formed as the main framework with plate‐like CaO·6Al2 O3 crystals mainly discontinuously embedded in MgO·Al2 O3 . The bulk density of AMC composite is up to 3.42 g/cm 3, equivalent to 90.5% of the theoretical density. The synthesized compact AMC composite in the work also exhibits better slag penetration resistance than the castable based on tabular corundum due to the formation of liquid phase.